Effect of seaweed on gastrointestinal microbiota isolated from Norwegian White sheep. (2nd July 2016) - Novoa-Garrido, M.; Rebours, C.; Aanensen, L.; Torp, T.; Lind, V.; Steinshamn, H.
ABSTRACT: The effects of a commercial seaweed (SW) product and extracts collected from wild SWs in the Northern Norway on cultivable commensal intestinal bacterial groups isolated from Norwegian White sheep ewes were studied in vivo and in vitro . Bacterial counts from faeces from the ewes fed with supplement which contained SW meal throughout the entire indoor winter period had significantly lower lactic acid bacteria (LAB) counts ( P  ≈ .05). The screening of extracts from red and brown SWs showed that a number of the organic extracts had an inhibitory effect on the growth of the two Enterococcus sp. isolates. The results indicate that Ascophyllum nodosum supplementation reduces LAB counts in the ewes and the lambs, and that extracts from this SW have an inhibitory effect on the growth of Enterococcus sp. isolates.